Clustering elementary education students' literacy skills as a key aspect of interaction with digital media on writing ability - Mulyati, Mulyati; Suryoputro, Gunawan; Tarmini, Wini (Edelweiss Applied Science and Technology, 2025)
Writing skills for descriptive texts are essential for helping students effectively convey their ideas. Many students still struggle to construct descriptive sentences and to utilize digital technology as a learning medium. This study examines the effect of digital media and its interaction with elementary education students' literacy levels on writing skills. The research employs a 2x2 factorial experimental design to generate four different treatment groups, specifically digital media tools (Sketchbook and IbisPaint X) and students' literacy levels (high and low). The results indicate a significant difference in writing skills between users of Sketchbook and IbisPaint X, with high-literacy students demonstrating a greater ability to utilize the media more creatively and structurally. Conversely, low-literacy students showed better results when using Sketchbook compared to IbisPaint X. The findings also reveal a significant interaction between the learning media and literacy level, where the difference in media effectiveness is more pronounced among low-literacy students, while the difference is less noticeable among high-literacy students. The conclusion of this study is that there is a significant difference in descriptive text writing skills between users of Sketchbook and IbisPaint X, influenced by literacy levels. Additionally, there is a significant interaction between learning media and literacy level in supporting the improvement of students’ writing skills.